Formation, Microstructure, and Conductivity of a Novel Ga2S3-Sb2S3-AgI Chalcogenide System - Xinyu Huang (Nature Portfolio, 2018)
Abstract Novel glasses in a Ga2S3-Sb2S3-AgI system were prepared with a melt-quenching method, and their glass-forming region was identified. The maximum dissolvable AgI in glasses was 65 mol%. The thermal, optical, and structural properties of glasses were investigated as a function of AgI and Ga2S3 contents. The Ga2S3-Sb2S3-AgI glasses possess a wide region of transmission window (0.65−14 μm). An ionic conductivity of approximately 1.01 × 10−3 S/cm can be obtained for a 40 (0.8Sb2S3-0.2Ga2S3)-60AgI glass at an ambient temperature, and the ionic conductivity increased as temperature increased. The relative activation energy of Ag+ conduction was also calculated. These novel glasses show potential for the combined application of infrared optics and solid electrolytes.